Penguatan Pemahaman Masyarakat Lingkar Tambang Terhadap Program PPM di Kabupaten Halmahera Utara - Almun Madi; Arbi Haya; Hilda Alkatiri; Firman Firman; Syarifullah Bundang; Nurany Nurany; Dian Dwi Apriliyani Arsdin; George Belly Sahetapy; Alifianty Delila Imani (Universitas Negeri Gorontalo, 2026)
Mining activities require community empowerment efforts through the Community Development and Empowerment Program (PPM) so that its benefits can be optimally felt by the communities surrounding the mine. This activity aims to increase community understanding of the PPM program in Barumadehe Village and Tabobo Village, Malifut District, North Halmahera Regency. The method used was participatory socialization to village heads and community leaders, followed by Focus Group Discussions (FGD) with the sub-district and the PT Nusa Halmahera Minerals CSR team. The results showed that the level of community understanding consisted of 12% understanding, 47% quite understanding, 39% not understanding, and 2% not understanding. The community has also felt the benefits of PPM in the fields of education, health, infrastructure, and religion. This activity is effective as an initial step in increasing community understanding.